About the Economic Psychology of Public Debt - Thomas Döring; Ruven D. Oehmke (Intereconomics, 2019)
Among the various means of public financing, public debt is a significant as well as controversial instrument. Previous economic research has mainly focused on different politico-economic explanations for the continuous increase in public debt in many countries during the last decades. However, economic research has not conclusively answered why the excessive increase in public debt is so rarely challenged by citizens and politicians despite the resulting budgetary burden. The answer to this question lies to some degree in economic psychology and the findings of behavioural economics.
Keywords: 330